Project: ArctiChildren - Öhrling, Kerstin; Alerby, Eva; Kostenius, Catrine; Forsman, Arne (Luleå tekniska universitet, Hälsa och rehabilitering, 2011)
Utvecklings och forskningsprojekt för psykosocialt välbefinnande hos barn och ungdomar i den arktiska regionen Publikationer: A silent message is also a message; Schoolchildren from the north sharing their lived experience of health and well-being; Research with a child perspective; 'Friendship is like an extra parachute': reflections on the way schoolchildren share their lived experiences of well-being through drawings; Giving voice and space to children in health promotionc; Status: Avslutat; Period: 01/12/2003 → 30/11/2006